THE EFFECT OF IMPLEMENTATION OF FLIPPED CLASSROOM TO ENHANCE STUDENT SPEAKING ABILITY IN APOLLONIA HOTEL SCHOOL - Ni Made Kristianti; Luh Putu Artini; I.G.A Lokita Purnamika Utami (IKIP Siliwangi, 2023)
This study aims to determine the effect of implementing flipped classrooms in teaching speaking skills at the Apollonia Hotel School in Denpasar. The research used quantitative research that implemented a quasi-experimental design with a pre-test and post-test. The population of this study consisted of 61 students from a hospitality school. They were into two classes: 30 students as an experimental group (taught speaking with a flipped classroom model) and 31 as a control group (taught speaking with conventional teaching). The teacher conducted the same subject material for both classes. Purposive sampling was used as the technique of this study. The instruments used in this study were a speaking test and a questionnaire. The analysis of speaking achievements with quantitative data using an independent sample t-test. The result showed significant differences in implementing the flipped classroom in student speaking achievement: the experimental group scored higher than the control group. Keywords: Speaking; Flipped Classroom; Perception